Reatividade e eficiência agronômica do verdete e verdete calcinado como fertilizantes multinutrientes no arroz inundado - Arrieta, Rafael Gómez (2017)
Brazil imports a large volume of potassic fertilizers, which has fostered the need to find alternative potassium sources. Multinutrient sources are sought for crops of great importance, such as flooded rice. The objective of the present study was to evaluate the agronomic efficiency of the Verdete powder as a K, Si, Mg and Mn source, fine-grained Verdete as a source for K, Si, Ca and Mg in flooded rice, and compared to the Potassium chloride (KCl), calcium silicate (Wollastonite) and manganese sulphate (MnSÜ4). The greenhouse experiments were conducted in a red Oxysol (LVd) as well as an Ustoxic Quartzipsamment soil (RQo). The experimental design consisted in a randomized block design with four replications, the treatments consisted of increasing K2O doses provided by Verdete powder, as well as fine-grained Verdete which also corresponded to Si rates. Besides these, other treatments were used and considered as standard for K (KCl), Si (Wollastonite), Mn (MnSÜ4) and a control without the K2O application. The sources were applied 90 days before sowing the rice, which was planted in pots with air dried soil, with humidity elevated to 80% of field capacity during incubation. The agronomic efficiency index was determined (IEA) considering KCl and Wollastonite as well as the percentage of recovered K. 75 days after planting, tillering was evaluated (Per) and, at harvest, plants were cut at the soil level, the panicles were separated and counted, which generated the number of panicles (Pan). All the plant material was oven dried and weighed for shoot dry matter (MSP) and grain dry matter (MSG) determination. Soil analysis determined the soil pH and the K, Si, Ca, Mg and Mn content. The same determinations, except pH, were also made on vegetal material and these results, multiplied by MSP resulted in the accumulation of these nutrients. The IEA and the percentage of K recovered from Verdete powder were higher in LVd than in RQo. In both soils, Pan, MSP, MSG, the K, Si, K and Mg releasing and shoot accumulation, as well as the IEA, of the treatments with Verdete powder did not reach the observed levels for the standard fertilizers and were higher in the treatments with fine-grained Verdete compared to the microgranulate one with greater accumulation of K, Si and Ca. In both soils, increasing Verdete rates resulted in reduction of soil Mg and Mg accumulation for both soils, and reached critical deficiency levels. The application of increasing doses of calcined Verdete decreased the pH and the Mg content in the soil, with emphasis on the fine-grained calcined Verdete, which acted more intensely on the soil acidity.